Influence of Weather Conditions on COVID-19 Case in Several Regions of Indonesia - Bella Deswanti; Marzuki Marzuki; Robi Muharsyah; Helmi Yusnaini; Ravidho Ramadhan (Jurnal Penelitian Pendidikan IPA, 2022)
This study investigates the relationship between COVID-19 and weather conditions in six regions in Indonesia, namely South Jakarta, East Jakarta, North Jakarta, Jember Regency, Semarang City, and West Pasaman Regency. The study uses the daily number of positive cases of COVID-19 and weather data. Weather parameters used in this study are the average, maximum, and minimum temperature, rainfall, and relative humidity. Weather data were obtained from surface observation of Agency for Meteorology, Climatology and Geophysics (BMKG) and reanalysis product (ERA-5) from European Centre for Medium-Range Weather Forecasts (ECMWF). The effect of weather conditions on the number of COVID-19 cases was evaluated using the Spearman and Kendall correlation. It was found that the number of positive cases of COVID-19 had a relationship with weather parameters. A negative correlation was found between the temperature and the number of positive COVID-19 cases. Thus, the number of positive COVID-19 cases increases when the temperature decreases. On the other hand, rainfall and relative humidity positively correlate to the number of positive cases of COVID-19, which means that when the rainfall and relative humidity increase, the number of positive cases of COVID-19 increases. The relationship between weather conditions and the number of COVID-19 cases is more apparent in areas with a higher population density, such as Jakarta. The results of this study can be valuable information in handling COVID-19 cases.